Bulgaria : Does Making Early Education Free Benefit Disadvantaged Children? - World Bank (World Bank, Washington, DC, 2018)
In Bulgaria, school is now compulsory for children aged five and six-years-old (known as preschool for children in this age group) and the government offers full-day and half-day programs. Full-day programs, which are preferred by most families, charge about 176 Bulgarian lev a year. Half-day programs are free, but families are often asked to contribute monthly to cover transportation, food and school supplies. Because the number of full-day slots is limited, families that want to ensure availability enroll their children in schools’ preschool programs at age three or four, which guarantees them a kindergarten slot when they’re older. But school at this age isn’t free. Thus, poor families in Bulgaria may be less likely to take advantage of early education programs when their children are younger, making it harder for them to find full-day slots when their children are ready to start at age five. A 2011 European Union regional studylooking at the situation of Roma populations in Bulgaria, Hungary, Romania, Slovakia and the Czech Republic found that while more than 75 percent of children aged three to six years old were in a preschool program, about 55 percent of Roma children weren’t. The Bulgarian-based Trust for Social Achievement, a local non-governmental organization created by the America for Bulgaria Foundation to fund programs for economically disadvantaged people, including Roma, worked with SIEF-supported researchers to design and evaluate strategies for increasing early childhood education participation among the poorest families in Bulgaria.